PERANCANGAN APLIKASI PENJUALAN UNTUK UMKM PADA MASA PANDEMI COVID-19 DAN NEW NORMAL - Abd Wahab Syahroni; Ustman Ustman; Nilam Ramadhani (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
The implementation of social distancing in Pamekasan Regency as an action to prevent the spread of the COVID-19 virus has caused changes in the way people shop. The use of technology needs to be utilized by both the community and MSME actors so that buying and selling transactions can continue as usual. Basically, online buying and selling transactions are not new anymore, unfortunately ASLMART Minimarket MSMEs do not yet have an online sales application. This study intends to design an online sales application based on the problems that exist in the ASLMART Minimarket. Waterfall is used as a software development method, testing application functionality using the blackbox method. This research produces a responsive web-based sales application and is expected to be implemented to help increase sales transactions at the ASLMART Minimarket during the pandemic and new normal.